Uji Kinerja Alat Chopper Serbaguna Untuk Merajang Batang Singkong Varietas Bayeman - Asmara, Sandi; Tamrin, Tamrin; Zakaria, Rizky (Jurnal Agricultural Biosystem Engineering, 2025)
Cassava production not only produces tubers and leaves that can be used asvegetables, but there is also waste produced, one of which is cassava stems. Sofar, cassava stem waste has not been widely utilized by farmers, so after thecassava is harvested, the cassava stems are just left lying on the land. This studyaims to reduce cassava stem waste by reducing the size using a multi-purposeChopper tool with several variations in engine rotation per minute (RPM). Thisresearch was conducted at the Agricultural Machinery and Equipment PowerLaboratory, Department of Agricultural Engineering, Faculty of Agriculture,University of Lampung in March 2025. The treatment used 3 variations of RPM,namely 1500, 1800, and 2100 where each used 3 different input amounts, namely:input of 3 stems, 4 stems, and 5 stems and each RPM was repeated 3 times. Theresults showed that chopping using the RPM setting of 2100 and the input amountof 4 cassava stems had the best work capacity with a value of 150.8 kg/hour. Thelowest fuel consumption using RPM variation of 1500 and the amount of input of3 sticks with a value of 591.6 ml/hour.